Climate change reshapes the drivers of false spring risk across European trees. Issue 1 (5th September 2020) - Chamberlain, Catherine J.; Cook, Benjamin I.; Morales‐Castilla, Ignacio; Wolkovich, E. M.
Summary: Temperate forests are shaped by late spring freezes after budburst – false springs – which may shift with climate change. Research to date has generated conflicting results, potentially because few studies focus on the multiple underlying drivers of false spring risk. Here, we assessed the effects of mean spring temperature, distance from the coast, elevation and the North Atlantic Oscillation (NAO) using PEP725 leafout data for six tree species across 11 648 sites in Europe, to determine which were the strongest predictors of false spring risk and how these predictors shifted with climate change. All predictors influenced false spring risk before recent warming, but their effects have shifted in both magnitude and direction with warming. These shifts have potentially magnified the variation in false spring risk among species with an increase in risk for early‐leafout species (i.e. Aesculus hippocastanum, Alnus glutinosa, Betula pendula ) compared with a decline or no change in risk among late‐leafout species (i.e. Fagus sylvatica, Fraxinus excelsior, Quercus robur ). Our results show how climate change has reshaped the drivers of false spring risk, complicating forecasts of future false springs, and potentially reshaping plant community dynamics given uneven shifts in risk across species.